1991
DOI: 10.1007/bf03350268
|View full text |Cite
|
Sign up to set email alerts
|

One year treatment with clonidine in children with constitutional growth delay

Abstract: The therapeutic potential of clonidine was evaluated in 112 prepubertal children with short stature, delayed bone age and a growth velocity of 4.1 +/- 0.4 cm/yr in boys and 4.2 +/- 0.5 cm/yr in girls. The alpha 2 agonist was orally administered at 0.075 mg/m2 to 51 boys and 39 girls over a period of at least one year, and the effect compared to a vitamin treatment given to 10 age matched boys and 12 age matched females showing similar growth velocities. After one year of treatment growth velocity was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…m -2 for one year has been reported in 90 children with constitutional growth delay. 21 These investigations appear to indicate the safety of clonidine for children at the dose used in the present study. Furthermore, an anecdotal report has revealed that there were no deaths in 11 toddlers ingesting clonidine accidentally in doses Of I0-150 I~g" kg-l. 22 This episode also relieves us of our anxiety that clonidine 4 ~g.…”
Section: Discussionsupporting
confidence: 54%
“…m -2 for one year has been reported in 90 children with constitutional growth delay. 21 These investigations appear to indicate the safety of clonidine for children at the dose used in the present study. Furthermore, an anecdotal report has revealed that there were no deaths in 11 toddlers ingesting clonidine accidentally in doses Of I0-150 I~g" kg-l. 22 This episode also relieves us of our anxiety that clonidine 4 ~g.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly in a prospective study by DorantesAlvarez et al clonidine administration in children with familial or constitutional growth short stature, increased height velocity in both groups [23]. Moreno Esteban et al and Calzolari et al [24,25] also claimed that clonidine was helpful in increasing growth velocity of patients with constitutional growth delay. Above disagreement and discrepancies of studies results, may be due to differences in baseline characteristic in studies populations, causes of short stature, different clonidine prescription and additional treatment with vitamins or calcium replacement in some studies.…”
Section: Discussionmentioning
confidence: 93%